ACETAMINOPHEN TOXICITY AND ITS SUCCESSFUL MANAGEMENT IN A PUG DOG - A CASE REPORT - G.R. Baranidharan,; B.R. Baby Roshini,; C. Jayanthy,; A. Gopalakrishnan,; Arjun V Thampi,; G.Vijayakumar, (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A pug dog was presented to Small Animal Outpatient Unit of Madras Veterinary College with the history of oral administration of 2.5 tablets of 500 mg acetaminophen. Physical examination of animal revealed a dull and depressed with pale mucous membrane. Haematological values were within normal range and biochemistry report revealed elevated Alanine amino transferase enzyme which indicated the hepatotoxic adverse effect of acetaminophen. Normal saline was administered intravenously. N-acetyl Cystine was administered @140 mg/kg intravenously after diluting in 5% dextrose. The owner was advised to give oral N-Acetyl cystine tablets at a dose rate of 70 mg/kg after 6 hrs and to repeat as such seven times. Oral liver supplements containing S-Adenosyl methionine and silybin was prescribed and advised to give at the dose rate of 5 ml/10 kg body weight. Hematinics was prescribed and advised to give orally at a dose rate of 2.5 ml/5 kg body weight twice daily.